CYP2C19*17 protects against metabolic complications of clozapine treatment. (3rd October 2017) - Piatkov, Irina; Caetano, Dorgival; Assur, Yolinda; Lau, Sue Lynn; Coelho, Micheline; Jones, Trudi; Nguyen, Tristan; Boyages, Steven; McLean, Mark
Abstract: Objectives: Clozapine (CZ) is the most effective drug for managing treatment-resistant schizophrenic disorders. Its use has been limited due to adverse effects, which include weight gain and new-onset diabetes, but the incidence of these varies between patients. Methods: We investigated 187 Clozapine Clinic patients (of whom 137 consented for genotyping) for the presence of CYP2C19*17 and its association with CZ and norclozapine (NCZ) levels, and clinical outcomes. Results: Thirty-nine percent of genotyped patients were carriers of the CYP2C 19*17 polymorphism. This group demonstrated significantly higher NCZ serum levels, and significantly lower fasting glucose (5.66 ± 1.19 vs 6.72 ± 3.01 mmol/l, P = 0.009) and Hb1Ac (35.36 ± 4.78 vs 49.40 ± 20.60 mmol/mol, P = 0.006) levels compared to non-carriers of this polymorphism. CZ-treated patients with CYP2C19*17/*17 had a significantly lower prevalence of diabetes as well as a higher likelihood of clinical improvement of their schizophrenia, compared to those without this polymorphism ( P = 0.012 and P = 0.031, respectively). Conclusions: Our data suggest that CYP2C19*17 ultra-rapid-metaboliser status is a protective factor against the development of diabetes during clozapine treatment, and increases the likelihood of improvement in schizophrenia. The role of NCZ in treatment response and side effects, including metabolic syndrome, warrants further pharmacogenetic, pharmacokinetic and pharmacodynamic studies.